2017
DOI: 10.5380/ce.v22i3.49501
|View full text |Cite
|
Sign up to set email alerts
|

Identificação Do Paciente Em Neonatologia Para Assistência Segura

Abstract: RESUMO: Estudo transversal, observacional, documental, abordagem quantitativa, realizado numa Unidade Neonatal de um Hospital Universitário do Rio de Janeiro, no período de maio e agosto de 2016. Analisou a identificação de pacientes neonatos por meio de pulseira. Foram realizadas 200 observações; constatou-se que em 155 (77,5%), os neonatos apresentavam pulseiras de identificação. Quanto à localização, 91 (58,7%) delas estavam em tornozelos ou punhos; quanto à legibilidade dos descritores, 76 (83,5%) apresent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 7 publications
0
5
1
8
Order By: Relevance
“…8 A study performed at a neonatal unit of a university hospital in Rio de Janeiro City analyzed 200 NB identification wristbands and found that 25.5% of NB were not wearing them. 5 This result was already higher than the results found in this study. In Brazil, it is perceived that health professionals still fail to guarantee the goal of 100% identification of NB, although the institutional protocol describes steps that guide these professionals to identify all patients at the time of birth or hospitalization.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…8 A study performed at a neonatal unit of a university hospital in Rio de Janeiro City analyzed 200 NB identification wristbands and found that 25.5% of NB were not wearing them. 5 This result was already higher than the results found in this study. In Brazil, it is perceived that health professionals still fail to guarantee the goal of 100% identification of NB, although the institutional protocol describes steps that guide these professionals to identify all patients at the time of birth or hospitalization.…”
Section: Discussioncontrasting
confidence: 69%
“…It is possible to find in the literature some special cases that justify the non-wearing of wristbands, being: NB with gestational age ≤ 37 weeks or neonates with upper or lower limb edema, malformation syndromes or allergy to the wristband material. 5 However, the institutional protocol did not join these recommendations, and in all cases, it is necessary to identify NB in another member (in cases of pathologies) or to execute wristband adjustment (in preterm/low birth weight NB).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concernente aos dados da unidade de terapia intensiva neonatal, a qual apresentou 81,6 % de adesão à pulseira identificadora, há estudo com resultados similares, sendo este realizado em uma UTI neonatal do Rio de Janeiro, que constatou que 77,5% dos neonatos apresentavam pulseiras de identificação (17) . A mesma pesquisa citada refere que uma possibilidade de justificativa para a não adesão em alguns casos ao uso da pulseira de identificação pode ser o fato de alguns neonatos permanecerem por muito tempo internados, o que gera nos profissionais de enfermagem, em especial, a sensação do conhecer o paciente (17) , o que sem dúvida é preocupante, pois a falha humana é inerente ao trabalho em saúde.…”
Section: Discussionunclassified
“…A mesma pesquisa citada refere que uma possibilidade de justificativa para a não adesão em alguns casos ao uso da pulseira de identificação pode ser o fato de alguns neonatos permanecerem por muito tempo internados, o que gera nos profissionais de enfermagem, em especial, a sensação do conhecer o paciente (17) , o que sem dúvida é preocupante, pois a falha humana é inerente ao trabalho em saúde. Isso porque, a ausência de identificação do paciente pode promover eventos adversos graves, tais como erros na realização de procedimentos, na administração de medicamentos ou hemoderivados e até mesmo a troca de bebês (17) .…”
Section: Discussionunclassified